Standards : recipes for reality - Busch, Lawrence (Infrastructures series., 2011)
This book investigates standards as the recipes that shape not only the physical world, but human social interactions. The author outlines the history of formal standards and describes how modern science came to be associated with the moral-technical project of standardization of both people and things. The author also explores how standards are intimately connected to power, empowering some but disempowering others.